2005
DOI: 10.1890/04-1283
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Defensive Strategies of Young Leaves in Two Species of Inga

Abstract: Abstract. In the recently radiated genus Inga (Fabaceae), few nucleotide substitutions have accumulated among species, yet large divergences have occurred in defensive phenotypes, suggesting strong selection by herbivores. We compared herbivory and defenses of young leaves for I. goldmanii, a more derived species that follows a ''defense'' strategy, and I. umbellifera, a more basal species that follows an ''escape'' strategy. The two species suffered similar rates of herbivory (22% of the leaf area eaten durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 41 publications
1
81
1
2
Order By: Relevance
“…An Inga-specific fractionation protocol (Fig. S5) developed in the lab at the University of Utah produced seven chemically distinct (19,47) fractions: lipids, phenolics, saponins, amino acids, organic acids, proteins, and the insoluble parts of the cell walls (marc). Two of these, phenolics and saponins, either have been shown to account for the great majority of the deterrent activity in Inga extracts (19,47) or are presumed to be deterrent based on their mass abundance and the literature (27).…”
Section: Methodsmentioning
confidence: 99%
“…An Inga-specific fractionation protocol (Fig. S5) developed in the lab at the University of Utah produced seven chemically distinct (19,47) fractions: lipids, phenolics, saponins, amino acids, organic acids, proteins, and the insoluble parts of the cell walls (marc). Two of these, phenolics and saponins, either have been shown to account for the great majority of the deterrent activity in Inga extracts (19,47) or are presumed to be deterrent based on their mass abundance and the literature (27).…”
Section: Methodsmentioning
confidence: 99%
“…Other terpenoids found in relevant concentrations were linalool (2, 5.17%), α-terpineol (3, 4.18%), geraniol (4, 3.71%) and γ-eudesmol (5, 3.48%) (Figure 1). In addition to terpenoids, the major compounds identified in this essential oil were hexadecanol (6, 8.34%), heptadec-8-ene (7, 7.66%), homosalate (8,4.60%), hexadecane (9, 4.57%) and phytone (10, 3.90%) (Figure 1 In the leaves' essential oil, a total of 22 compounds were identified for the same season ( Table 1). Most of the compounds identified were esters, representing 42.35% of the total, while the bark's essential oil accounted for 10.88% ( Table 2).…”
Section: Yield and Chemical Composition Of The Essential Oilsmentioning
confidence: 98%
“…Several species of Inga are used in folk medicine as an anti-inflammatory, an antidiarrheal and a nasal decongestant, and for skin treatment, earache and cleaning teeth [1,2]. Studies of these species have reported the isolation of some metabolites such as depsides [3], metabolites of nitrogen [4], pipecolic acids [5,6], steroidal glycosides [7] and phenolic compounds [1,[7][8][9][10][11]. However, there are few chemical studies available related to I. laurina species [12].…”
Section: Introductionmentioning
confidence: 99%
“…G. Dexter, unpublished data) and used the following primers for amplification: ITS 4 (White et al 1990) and ITS 5a (Stanford et al 2000). We selected the trnD-trnT region because it contained the highest number of polymorphic sites among multiple chloroplast intergenic regions that were initially screened in the genus (Coley et al 2005; R. T. Pennington, unpublished data). We amplified the trnD-T region using the following primers: trnH (trnT in Demesure et al 1995) and trng2 (Oh and Potter 2003).…”
Section: Dna Sequencesmentioning
confidence: 99%